Quantitative assessment of the surface crack density in thermal barrier coatings - Yang, L.; Zhong, Z.; Zhou, Y.; Lu, Chunsheng (Springer, 2014)
In this paper, a modified shear-lag model is developed to calculate the surface crack density in thermal barrier coatings (TBCs). The mechanical properties of TBCs are also measured to quantitatively assess their surface crack density. Acoustic emission (AE) and digital image correlation methods are applied to monitor the surface cracking in TBCs under tensile loading. The results show that the calculated surface crack density from the modified model is in agreement with that obtained from experiments. The surface cracking process of TBCs can be discriminated by their AE characteristics and strain evolution. Based on the correlation of energy released from cracking and its corresponding AE signals, a linear relationship is built up between the surface crack density and AE parameters, with the slope being dependent on the mechanical properties of TBCs.